One Year Serum Albumin is an Independent Predictor of Outcomes in Kidney Transplant Recipients - Dahlberg, Rebecca (2010)
OBJECTIVE: This research study was conducted to investigate whether serum albumin levels predict allograft/patient outcomes in the new era of transplant medicine and immunology. METHODS: The association of 1-year post transplant serum albumin and patient and graft outcomes was retrospectively analyzed in 500 kidney transplant recipients between 1998 and 2005. Albumin was used as a categorical and a continuous variable in univariate and multivariate Cox regression and Kaplan-Meier survival analyses. RESULTS: The average (± SE) age at transplant was 47 ± 12 years. Patients were followed for 63.4 ± 28 months after transplant. There were 56 graft losses and 38 patient deaths. In univariate analysis, the following variables were associated with the composite endpoint of patient death or allograft loss: one-year serum albumin (HR 0.52, p=0.0009), one-year serum albumin < 4.0 g/dL (HR 1.81, p=0.02), one-year serum creatinine (HR 3.55, p <0.00001), ACE-I/ARB use (HR 1.61, p=0.03), a history of previous transplant (HR 1.54, p=0.04), months of dialysis before transplant (HR 1.01, p=0.00003), type of transplant (deceased donor HR 1.64, p=0.02) and acute rejection (HR 1.52, p=0.0000003). Of these, multivariable Cox regression analyses retained one-year serum albumin (HR 1.4, p<0.0001), serum creatinine (HR 2.7, p<0.0001) and acute rejection (HR 1.7, p=0.02) as significant predictors of patient/graft loss. CONCLUSION: One-year serum albumin is an independent predictor of poor outcomes in the contemporary era of transplant medicine and immunosuppression. Further studies are needed to separate the role of this biomarker in inflammation and nutrition in kidney transplant recipients.